Open the Progressive case for free trade, immigration, and global capital - Clausing, Kimberly A. (Harvard University Press, 2019)
With the winds of trade war blowing as they have not done in decades, and left and right agreeing only on protectionism, a leading economist forcefully shows how a free and open economy is still the best way to advance the interests of working Americans.--